A rare case of duplication of the descending colon in a pregnant woman: case report and literature review - Cherchi, Vittorio; Intini, Sergio; Velkoski, Jaqueline; Calandra, Sergio; Ventin, Marco; Della Martina, Monica; Lorenzin, Dario; Driul, Lorenza; Terrosu, Giovanni (Acta Biomedica Atenei Parmensis, 2023)
Introduction: Gastrointestinal duplications are uncommon congenital abnormalities that can occur anywhere throughout the intestinal tract. The small bowel is more interested than the large one. Duplications are schematically classified as spherical and tubular, respectively representing 80% and 20% of cases, with different relationships and communications with the native intestinal wall. Although typically diagnosed during infancy and early childhood, tubular colonic sub-type stays frequently hidden for several years until a complication occurs.Case presentation: we report the case of a T-shaped tubular duplication in a 20-year-old woman at the 30th week of gestation, who underwent an urgent exploratory laparotomy for intestinal occlusion, treated with the resection of the aberrant large bowel. The patient was notable for a long history of constipation and chronic pain. Diagnostic possibilities were limited by the on-going pregnancy.Conclusion: Intestinal duplications are uncommon malformations, and, of these, the T-shaped subtype of the colon is among the rarest ones. In the adulthood, diagnosis is usually established in the operating room during urgent or even emergency surgery performed for abdominal complications. A duplication of the descending colon is extremely rare, and this is, to our knowledge, the only article describing a case found in advanced state of pregnancy.